Knowledge And Attitude of Store Owners In Kampung Pisang Urban Village Towards Expired Food - Sakriani, Sakriani; Wahyu Purwiningsih, Dwi; M. Saleh, Fatmah; A. K. Stoffel, Hardiyanti (Universitas Muhammadiyah Palu, 2019)
Food poisoning and infectious disease that were caused by food tend to be increased. One of the causes was food expired intake. The purpose of the study was to know the knowledge and attitude of stall owners toward expired food. This was an observational study. Sample size of the study 30 respondents. The result suggested that 50% of 30 respondents has a good level of knowledge and the rest 50% has enough knowledge about food expired, none of respondents has a poor level of knowledge. It could be concluded that both respondent whose knowledge level was good and enough were same. All respondent has a good attitude towards food expired. It would be better if the next study explores about consumer knowledge and behavior towards food expired because the final decision of food expired consumption is on the consumer hand.